Penerapan Pendekatan Jelajah Alam Sekitar dengan Model Pembelajaran Kooperatif Tipe Stad untuk Meningkatkan Hasil Belajar Siswa pada Materi Pencemaran Lingkungan di Kelas X SMA Kosgoro Serei: Penelitian - Mei Delin Villia Nangkoda; Mercy Maggy Franky Rampengan; Aser Yalindua (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to evaluate the effectiveness of the JAS (Exploration of the Surrounding Environment) approach and the STAD (Student Teams Achievement Division) type of Cooperative Learning Model in improving students' learning outcomes in biology subjects. The results of the study indicate that in Cycle I, out of a total of 15 students, 10 students had not yet met the Minimum Mastery Criteria (MMC), with a percentage of 66.67%. In Cycle II, only 2 out of 15 students had not reached the MMC, representing 13.34%, while the remaining 13 students achieved the MMC, accounting for 86.66%. These findings demonstrate an improvement in student learning outcomes following the implementation of the applied learning models. The conclusion of this study contributes to the development of more effective instructional methods to enhance student achievement and provides insights for educators in designing instruction that aligns with students' needs and interests.